Low Countries Women as Funders of Art and Architecture: Gender, Property Rights, and the Financing of the Flemish Baroque - Moran, Sarah Joan (Early Modern Low Countries, 2025)
From the late sixteenth century into the early eighteenth, the Southern Low Countries constituted one of the most important regions for artistic production and exchange in Europe. This essay reveals the understudied roles of women in the flourishing of that visual culture. I argue that this topic must be approached with a solid understanding of the gendered property laws and practices that shaped both how women used their wealth to finance art and architecture, and the sources through which we access that activity.